A kind of alumina porous ceramic material and its preparation method and application

By using large-grain corundum sand with controllable particle size and aluminum dihydrogen phosphate and other materials, alumina porous ceramic materials were prepared, which solved the problem of insufficient gas flowability and adsorption capacity of vacuum suction cups when dealing with thicker silicon wafers, and achieved Ceramic materials with high strength, hardness and adsorption properties are suitable for high-performance vacuum suction cups.

CN118724565BActive Publication Date: 2025-02-18ZHONGKE JINCI (NINGBO) NEW MATERIALS TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410790621.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-02-18
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

When existing vacuum suction cups deal with thicker silicon wafers, it is difficult to ensure gas flowability and adsorption force. At the same time, there are problems of insufficient hardness and strength, resulting in poor processing accuracy of silicon wafers and contamination of suction cups.

Method used

Large-grain corundum sand with controllable particle size is used as raw material, aluminum dihydrogen phosphate is used as binder, combined with powdering, dry press forming and sintering processes, alumina porous ceramic materials are prepared to ensure the controllable pore size, strength and High hardness.

Benefits of technology

It realizes the high adsorption performance, strength and hardness of alumina porous ceramic materials. It is suitable for vacuum suction cups with larger thickness, avoids powder loss and pollution problems, and extends the service life of suction cups.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118724565B_ABST
    Figure CN118724565B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of ceramic materials, and discloses an alumina porous ceramic material and a preparation method and application thereof. The present invention mixes corundum sand, a binder, a curing agent, paraffin wax and a pigment, and obtains a wax cake after heating and cooling the obtained mixture; the wax cake is powdered and sieved, and the obtained powder is dry-pressed to obtain a green body; the green body is sintered to obtain an alumina porous ceramic material. The present invention uses large-particle corundum sand with controllable particle size as raw material, and adjusts the alumina ceramic material by changing the particle size of the large-particle corundum sand, so as to achieve controllable pore size of the alumina ceramic material, and at the same time, the hardness, strength and adsorption performance of the alumina ceramic meet the requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic materials, and in particular to an alumina porous ceramic material and a preparation method and application thereof. Background Art

[0002] Semiconductor integrated circuit (IC) is the core technology of the electronics manufacturing industry. In the production process of IC, the silicon wafer used as the substrate needs to be transferred and processed many times. Compared with the traditional method of transferring silicon wafers by mechanical clamping and wax bonding, the method of using vacuum suction cups to transfer silicon wafers is popular because it does not damage the silicon wafer itself and can make the transfer more reliable.

[0003] The vacuum suction cup uses pressure difference to absorb objects. When using it to absorb the wafer, the air flows from the gap between the wafer and the porous ceramic into the pores, forming a pressure difference at both ends of the gap. If the porous ceramic is relatively thin, the smaller pore size can produce a greater adsorption force. When the thickness increases, the resistance to the flow of fine pores is greater, and a larger pore size is required to ensure that the flow of air produces a pressure difference.

[0004] Therefore, when preparing thicker vacuum suction cups, a larger pore size is required to ensure gas permeability and adsorption force. While meeting these two requirements, hardness and strength must also be guaranteed. If the vacuum suction cup is not strong enough, it may deform during use, resulting in the inability to guarantee the processing accuracy of the silicon wafer; and insufficient hardness will be directly manifested as powder loss, which will contaminate the wafer and affect the processing quality. During operation, ceramic vacuum suction cups are also susceptible to dust after grinding, resulting in problems such as uneven suction and contamination of the clamped object. Therefore, the surface layer is usually continuously ground off during use, and needs to be replaced after multiple uses, which is an important consumable.

[0005] With the development of the semiconductor industry, the market demand for vacuum chucks is becoming more and more vigorous. Therefore, it is quite necessary to study and prepare porous ceramics with uniform adsorption, high strength and hardness and use them for vacuum chucks. Summary of the invention

[0006] The object of the present invention is to provide an alumina porous ceramic material and a preparation method and application thereof. The alumina porous ceramic material has excellent hardness, strength and adsorption performance and low cost.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing an alumina porous ceramic material, comprising the following steps:

[0009] (1) corundum sand, a binding agent, a curing agent, paraffin and a pigment are mixed, and the resulting mixture is heated and cooled to obtain a wax cake;

[0010] (2) grinding the wax cake into powder and sieving to obtain a powder;

[0011] (3) dry-pressing the powder to obtain a green body;

[0012] (4) sintering the green body to obtain an alumina porous ceramic material;

[0013] In step (1), the binder is aluminum dihydrogen phosphate; the particle size of the corundum sand is in the range of 120 to 220 meshes.

[0014] Preferably, in the above-mentioned method for preparing alumina porous ceramic material, in step (1), the mass ratio of the corundum sand, the binder, the curing agent and the paraffin is 4-20:1-3:0.01-3:1-4.

[0015] Preferably, in the above-mentioned method for preparing alumina porous ceramic material, the pigment includes copper chrome black, and the mass of the pigment is 1 to 3% of the mass of the corundum sand.

[0016] Preferably, in the above-mentioned method for preparing alumina porous ceramic material, in step (1), the curing agent is one or more of copper oxide, zinc oxide and titanium oxide.

[0017] Preferably, in the above-mentioned method for preparing alumina porous ceramic material, in step (1), the heating temperature is 90 to 150° C.; and the heating time is 10 to 30 minutes.

[0018] Preferably, in the above-mentioned method for preparing alumina porous ceramic material, in step (2), the total time of the powdering is 10 to 20 seconds; and the mesh size of the sieving screen is 40 to 100 meshes.

[0019] Preferably, in the above-mentioned method for preparing alumina porous ceramic material, in step (3), the pressure of the dry pressing is 10 to 200 MPa; and the holding time of the dry pressing is 10 s to 10 min.

[0020] Preferably, in the above-mentioned method for preparing alumina porous ceramic material, in step (4), the sintering temperature is 800-1000° C.; and the sintering time is 2-6 hours.

[0021] The invention also provides an alumina porous ceramic material prepared by a method for preparing the alumina porous ceramic material.

[0022] The present invention provides the application of the porous alumina ceramic material described in the above technical solution in a vacuum chuck.

[0023] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention uses large-particle corundum sand with controllable particle size as raw material, and controls the alumina ceramic material by changing the particle size of the large-particle corundum sand, so as to achieve controllable pore size of the alumina ceramic material. In addition, the present invention uses aluminum dihydrogen phosphate as a binder, combined with the powdering, dry pressing and sintering processes used in the present invention to ensure that the alumina ceramic has sufficient strength and hardness. In addition, the present invention uses large-particle corundum sand to form pores, which are relatively evenly distributed and have a high through-porosity, and have better adsorption performance, especially for thick-sized vacuum suction cups, which can provide larger pores to ensure gas circulation.

[0025] The present invention adopts large-particle corundum sand as raw material. Corundum itself has no sintering activity and needs a binder to assist sintering. However, the present invention uses aluminum dihydrogen phosphate as a binder, which can be dehydrated and condensed after being heated to form a three-dimensional network to coat the corundum particles, so that the corundum particles are stacked more tightly, the strength of the material and the uniformity of the pores are improved, and after being treated at a temperature greater than 800°C, a rhombus aluminum phosphate phase is formed and a dense neck is formed between the corundum particles, and Al-OP bonds can be formed with the oxidized atoms in the corundum; at the same time, corundum and aluminum phosphate are both aluminum-based compounds with better compatibility. Compared with bonding other non-aluminum oxide ceramics, the bonding force and stability are high, and the material can have sufficient hardness so that it does not fall off during use.

[0026] Furthermore, the present invention adopts metal oxide as a curing agent. The metal oxide can react with the POH bond in aluminum dihydrogen phosphate to form a bond in the form of POM (M is a metal atom), so that the original two-dimensional cross-linking becomes a three-dimensional cross-linking, which accelerates the curing of aluminum dihydrogen phosphate and can also improve the cohesive force, further improve the stacking of corundum particles, and further improve the strength of the material and the uniformity of the pores; paraffin wax, as a commonly used molding aid in the powder molding process, can improve the strength of the green body and reduce the corrosion of aluminum dihydrogen phosphate to the dry pressing mold.

[0027] Furthermore, the method for preparing the porous alumina ceramic material of the present invention can reduce the sintering temperature of the green body to between 800 and 1000° C., which is a technology for low-temperature sintering of corundum-based porous materials. The finished product can be obtained by rapid sintering after wax removal. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a structural schematic diagram of a vacuum adsorption force testing device;

[0029] Figure 2 This is a scanning electron microscope image of the alumina porous ceramic material prepared in Example 2. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing an alumina porous ceramic material, comprising the following steps:

[0031] (1) corundum sand, a binding agent, a curing agent, paraffin and a pigment are mixed, and the resulting mixture is heated and cooled to obtain a wax cake;

[0032] (2) grinding the wax cake into powder and sieving to obtain a powder;

[0033] (3) dry-pressing the powder to obtain a green body;

[0034] (4) sintering the green body to obtain an alumina porous ceramic material;

[0035] The binder in step (1) is aluminum dihydrogen phosphate; the particle size of the corundum sand is in the range of 120 to 220 meshes.

[0036] In the present invention, the mass ratio of the corundum sand, the binder, the curing agent, and the paraffin in step (1) is preferably 4-20:1-3:0.01-3:1-4, more preferably 8-17:1-1.7:0.5-2:2-3.5, and more preferably 13:1.3:0.6:3. The present invention controls the amount of the binder and the curing agent to control the density and porosity of the porous ceramic within a suitable range, thereby obtaining good air permeability and vacuum adsorption performance, avoiding excessive binder to form a ceramic coating and unable to form porous ceramics, and avoiding excessive curing agent addition that leads to failure of molding.

[0037] In the present invention, the particle size of the corundum sand in step (1) is 120-220 mesh, more preferably 90-150 mesh, and more preferably 120 mesh. The present invention uses large-particle raw material corundum sand to prepare alumina porous ceramics, avoiding the decrease in porosity and pore size caused by small-particle particles, thereby affecting the vacuum adsorption performance of alumina ceramics.

[0038] In the present invention, the curing agent in step (1) is preferably one or more of copper oxide, zinc oxide, and titanium oxide, more preferably copper oxide or zinc oxide, and more preferably copper oxide.

[0039] In the present invention, the pigment preferably includes copper chrome black, and the mass of the pigment is preferably 1-3% of the mass of the corundum sand, more preferably 1.5%. The present invention adds black pigment to ensure that the suction cup does not reflect stray light during use, thereby interfering with the process.

[0040] In the present invention, the heating temperature in step (1) is preferably 90-150°C, more preferably 90-130°C, and more preferably 100°C; the heating time is preferably 5-30 min, more preferably 10-25 min, and more preferably 20 min.

[0041] In the present invention, the total time of the powdering in step (2) is preferably 10 to 20 seconds, more preferably 12 to 18 seconds, and more preferably 15 seconds; the number of times of powdering is preferably 3 times.

[0042] In the present invention, the mesh size of the sieve in step (2) is preferably 40 to 100 meshes, more preferably 60 to 80 meshes, and more preferably 80 meshes.

[0043] In the present invention, the dry pressing pressure in step (3) is preferably 10 to 200 MPa, more preferably 12 to 40 MPa, and more preferably 24 to 36 MPa; the dry pressing time is preferably 10 s to 10 min, more preferably 15 to 50 s, and more preferably 20 to 30 s.

[0044] In the present invention, the sintering temperature in step (4) is preferably 800-1000°C, more preferably 860-900°C, and more preferably 880°C; the sintering time is preferably 2-6h, more preferably 3-5h, and more preferably 4h; the sintering heating rate is preferably 2-5°C / min, more preferably 2-4°C / min, and more preferably 3°C / min.

[0045] The present invention also provides an alumina porous ceramic material prepared by the method for preparing the alumina porous ceramic material described in the above technical solution.

[0046] The present invention provides the application of the porous alumina ceramic material in the above technical solution in a vacuum chuck. The present invention has no special limitation on the application method, and the porous alumina ceramic can be made into a vacuum chuck according to a method well known in the art.

[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Example 1

[0049] This embodiment provides a method for preparing an alumina porous ceramic material, comprising the following steps:

[0050] S11, 200g of 120-mesh corundum sand, 0.6g of copper oxide, 3g of copper chrome black, and 10g of paraffin are mixed, and 10g of aluminum dihydrogen phosphate is added and mixed evenly, and then heated to 90°C on a constant temperature heating table to melt the paraffin, and the heating table is turned off after continuous heating for 10min, and the temperature is naturally lowered to obtain a wax cake after cooling;

[0051] S12, pour the wax cake into a powdering machine, powder for 5 seconds each time, powder 3 times, and then pass through a 80-mesh sieve to obtain powder;

[0052] S13, dry pressing the powder at 36 MPa for 30 seconds to obtain a green body;

[0053] S14, sintering the green body at 800° C. for 2 h to obtain a porous alumina ceramic material.

[0054] The porous alumina ceramic material prepared by the above method has a porosity of 30.58% and a density of 2.59 g / cm 3 The average pore size is 84.32μm, the hardness is 86HRB, and the flexural strength is 18MPa.

[0055] use Figure 1 The test device shown is used to test the vacuum adsorption force of the porous alumina ceramic material prepared in this embodiment. Figure 1 The test device shown is composed of a vacuum pump and a vacuum chamber. The vacuum pump is used to evacuate air to reduce the air pressure in the vacuum chamber. The pressure difference between the vacuum chamber and the outside generates pressure directed to the vacuum chamber, so that the plastic sheet is adsorbed on the porous ceramic. The specific test steps are as follows: Place the sample in the fixture and seal the side with a safety film to ensure airtightness. Place a 25g plastic sheet on the sample. There is a pull ring on the plastic sheet. Connect it to the universal electronic testing machine with a rigid wire. Turn on the vacuum pump and wait until the vacuum gauge displays 1.3*10 -1 After the vacuum degree reaches Pa, turn on the universal electronic testing machine to test the tensile strength function, pull the plastic sheet upward, read the tensile force when the sheet is detached, divide it by the sheet area, and get the vacuum adsorption force.

[0056] The results show that the porous alumina ceramic material prepared in Example 1 has a -1 The vacuum adsorption force under the vacuum degree of Pa is 15N / cm 2 , the sample did not lose powder during the test process.

[0057] Example 2

[0058] This embodiment provides a method for preparing an alumina porous ceramic material, comprising the following steps:

[0059] S21, 200g of 120-mesh corundum sand, 0.6g of copper oxide, 3g of copper chrome black, and 10g of paraffin were mixed, and 10g of aluminum dihydrogen phosphate was added and mixed evenly, and then heated to 90°C on a constant temperature heating platform to melt the paraffin, and the heating platform was turned off after continuous heating for 10min, and the temperature was naturally lowered to obtain a wax cake after cooling;

[0060] S22, pour the wax cake into a powdering machine, powder for 5 seconds each time, powder 3 times, and then pass through a 80-mesh sieve to obtain powder;

[0061] S23, dry pressing the powder at 36 MPa for 30 seconds to obtain a green body;

[0062] S24, sintering the green body at 1000° C. for 2 h to obtain a porous alumina ceramic material.

[0063] The porosity of the porous alumina ceramic material prepared by the above method is 36.89% and the density is 2.40g / cm 3 , average pore size is 82.61μm, hardness is 88HRB, bending strength is 20MPa, 1.3*10 -1 The vacuum adsorption force at the vacuum degree of Pa is 14N / cm 2 , the sample did not lose powder during the test process.

[0064] Example 3

[0065] This embodiment provides a method for preparing an alumina porous ceramic material, comprising the following steps:

[0066] S31, 200g of 120-mesh corundum sand, 0.8g of titanium oxide, 3g of copper chrome black, and 20g of paraffin were mixed, and 10g of aluminum dihydrogen phosphate was added to mix evenly, and then heated to 90°C on a constant temperature heating platform to melt the paraffin, and the heating platform was turned off after continuous heating for 10min, and the temperature was naturally lowered to obtain a wax cake after cooling;

[0067] S32, pour the wax cake into a powdering machine, powder for 5 seconds each time, powder 3 times, and then pass through a 80-mesh sieve to obtain powder;

[0068] S33, dry pressing the powder at 24 MPa for 30 seconds to obtain a green body;

[0069] S34, sintering the green body at 900° C. for 2 hours to obtain a porous alumina ceramic material.

[0070] The porous alumina ceramic material prepared by the above method has a porosity of 34.7% and a density of 2.50 g / cm 3 , average pore size is 85.13μm, hardness is 90HRB, bending strength is 24MPa, 1.3*10 -1 The vacuum adsorption force at the vacuum degree of Pa is 14N / cm 2, the sample did not lose powder during the test process.

[0071] Example 4

[0072] This embodiment provides a method for preparing an alumina porous ceramic material, comprising the following steps:

[0073] S41, 200g of 120-mesh corundum sand, 1.44g of copper oxide, 3g of copper chrome black, and 20g of paraffin were mixed, and 24g of aluminum dihydrogen phosphate was added and mixed evenly, and then heated to 90°C on a constant temperature heating platform to melt the paraffin, and the heating platform was turned off after continuous heating for 10min, and the temperature was naturally lowered to obtain a wax cake after cooling;

[0074] S42, pour the wax cake into a powdering machine, powder for 5 seconds each time, powder 3 times, and then pass through a 80-mesh sieve to obtain powder;

[0075] S43, dry pressing the powder at 36 MPa for 10 seconds to obtain a green body;

[0076] S44, sintering the green body at 1000° C. for 2 h to obtain a porous alumina ceramic material.

[0077] The porous alumina ceramic material prepared by the above method has a porosity of 36.87% and a density of 2.41 g / cm 3 , average pore size is 67.24μm, hardness is 92HRB, bending strength is 29MPa, 1.3*10 -1 The vacuum adsorption force at the vacuum degree of Pa is 15N / cm 2 , the sample did not lose powder during the test process.

[0078] Example 5

[0079] This embodiment provides a method for preparing an alumina porous ceramic material, comprising the following steps:

[0080] S51, 200g of 120-mesh corundum sand, 1.2g of copper oxide, 3g of copper chrome black, and 20g of paraffin were mixed, and 17g of aluminum dihydrogen phosphate was added and mixed evenly, and then heated to 90°C on a constant temperature heating platform to melt the paraffin, and the heating platform was turned off after continuous heating for 10min, and the temperature was naturally lowered to obtain a wax cake after cooling;

[0081] S52, pour the wax cake into a powdering machine, powder for 5 seconds each time, powder 3 times, and then pass through a 80-mesh sieve to obtain powder;

[0082] S53, dry pressing the powder at 36 MPa for 10 seconds to obtain a green body;

[0083] S54, sintering the green body at 1000° C. for 2 hours to obtain a porous alumina ceramic material.

[0084] The porous alumina ceramic material prepared by the above method has a porosity of 36.87% and a density of 2.41 g / cm 3 , hardness 90HRB, average pore size 72.98μm, bending strength 18MPa, 1.3*10 -1 The vacuum adsorption force at the vacuum degree of Pa is 15N / cm 2 , the sample did not lose powder during the test process.

[0085] Example 6

[0086] This embodiment provides a method for preparing an alumina porous ceramic material, comprising the following steps:

[0087] S55, 94g of 90-mesh corundum sand, 0.6g of copper oxide, 3g of copper chrome black, and 10g of paraffin wax were mixed, and 6g of aluminum dihydrogen phosphate was added to mix evenly, and then heated to 90°C on a constant temperature heating table to melt the paraffin wax, and the heating table was turned off after continuous heating for 10min, and the temperature was naturally lowered to obtain a wax cake after cooling;

[0088] S56, pour the wax cake into a powdering machine, powder for 5 seconds each time, powder 3 times, and then pass through a 80-mesh sieve to obtain powder;

[0089] S57, dry pressing the powder at 12 MPa for 10 seconds to obtain a green body;

[0090] S58. Sinter the green body at 900° C. for 2 hours to obtain a porous alumina ceramic material.

[0091] The porosity of the porous alumina ceramic material prepared by the above method is 41.99% and the density is 2.20 g / cm 3 , average pore size is 114μm, bending strength is 16MPa, hardness is 80HRB, 1.3*10 -1 The vacuum adsorption force at the vacuum degree of Pa is 13N / cm 2 , the sample did not lose powder during the test process.

[0092] Example 7

[0093] This embodiment provides a method for preparing an alumina porous ceramic material, comprising the following steps:

[0094] S59, 92g of 220-mesh corundum sand, 0.6g of copper oxide, 3g of copper chrome black, and 10g of paraffin wax were mixed, and 8g of aluminum dihydrogen phosphate was added to mix evenly, and then heated to 90°C on a constant temperature heating table to melt the paraffin wax, and the heating table was turned off after continuous heating for 10min, and the temperature was naturally lowered to obtain a wax cake after cooling;

[0095] S60, pour the wax cake into a powdering machine, powder for 5 seconds each time, powder 3 times, and then pass through a 80-mesh sieve to obtain powder;

[0096] S61, dry pressing the powder at 12 MPa for 10 seconds to obtain a green body;

[0097] S62, sintering the green body at 900°C for 2h to obtain a porous alumina ceramic material.

[0098] The porous alumina ceramic material prepared by the above method has a porosity of 35% and a density of 2.55 g / cm 3 , average pore size is 42.31μm, bending strength is 20MPa, hardness is 92HRB, 1.3*10 -1 The vacuum adsorption force at the vacuum degree of Pa is 15N / cm 2 , the sample did not lose powder during the test process.

[0099] Figure 2 This is a scanning electron microscope image of the alumina porous ceramic material prepared in Example 2. Figure 2 It can be seen that there are neck connections between alumina particles, which ensures good strength and hardness.

[0100] Furthermore, it can be seen from the adsorption performance data that the alumina porous ceramics prepared by the present invention have good adsorption performance, which is precisely the effect brought about by the characteristics of uniform pore distribution and high through-porosity of the prepared alumina porous ceramics.

[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous alumina ceramic material, characterized in that: The alumina porous ceramic material is applied to a vacuum chuck, and the preparation method comprises the following steps: (1) corundum sand, a binding agent, a curing agent, paraffin and a pigment are mixed, and the resulting mixture is heated and cooled to obtain a wax cake; (2) grinding the wax cake into powder and sieving to obtain a powder; (3) dry-pressing the powder to obtain a green body; (4) sintering the green body to obtain an alumina porous ceramic material; Wherein, in step (1), the binder is aluminum dihydrogen phosphate; the particle size of the corundum sand is in the range of 120-220 mesh; Wherein, in step (1), the mass ratio of the corundum sand, the binder, the curing agent, and the paraffin is 4-20:1-3:0.01-3:1-4; Wherein, in step (4), the sintering temperature is 800-1000°C; The pigment includes copper chrome black, and the mass of the pigment is 1-3% of the mass of the corundum sand; In step (1), the curing agent is one or more of copper oxide, zinc oxide and titanium oxide.

2. The method for preparing a porous alumina ceramic material according to claim 1, characterized in that: In step (1), The heating temperature is 90-150° C.; and / or The heating time is 10 to 30 minutes.

3. The method for preparing a porous alumina ceramic material according to claim 2, characterized in that: In step (2), The total powdering time is 10 to 20 seconds; and / or The mesh number of the sieve is 40 to 100 meshes.

4. The method for preparing a porous alumina ceramic material according to claim 1 or 3, characterized in that: In step (3), The dry pressing pressure is 10-200 MPa; and / or The holding time of the dry pressing is 10s~10min.

5. The method for preparing a porous alumina ceramic material according to claim 1, characterized in that: The sintering time is 2 to 6 hours.

6. A porous alumina ceramic material, characterized in that: The alumina porous ceramic material is prepared by the method for preparing an alumina porous ceramic material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Large-particle porous ceramic and preparation method thereof

    CN113248259A

  • Preparation method of black microporous breathable antistatic ceramic plate

    CN116375495A

  • 3DP manufacturing method of aluminum oxide ceramic part

    CN117447190A